Brain structure and habitat: do the brains of our children tell us where they have been brought up? - Kühn, Simone; Banaschewski, Tobias; Bokde, Arun L. W.; Büchel, Christian; Quinlan, Erin Burke; Desrivières, Sylvane; Flor, Herta; Grigis, Antoine; Garavan, Hugh; Gowland, Penny; Heinz, Andreas; Ittermann, Bernd; et al. (NeuroImage, 2020)
Recently many lifestyle factors have been shown to be associated with brain structural alterations. At present we are facing increasing population shifts from rural to urban areas, which considerably change the living environments of human beings. To investigate the association between rural vs. urban upbringing and brain structure we selected 106 14-year old adolescents of whom half were exclusively raised in rural areas and the other half who exclusively lived in cities. Voxel-based morphometry revealed a group difference in left hippocampal formation (Rural > City), which was positively associated with cognitive performance in a spatial processing task. Moreover, significant group differences were observed in spatial processing (Rural > City). A mediation analysis revealed that hippocampal formation accounted for more than half of the association between upbringing and spatial processing. The results are compatible with studies reporting earlier and more intense opportunities for spatial exploration in children brought up in rural areas. The results are interesting in the light of urban planning where spaces enabling spatial exploration for children may deserve more attention.